Promoción de hábitos y estilos de vida saludable por medio de pausas activas en trabajadores administrativos de la empresa apuestas Ochoa s.a de la ciudad de armenia. (2016)
The project consisted in promoting healthy habits and lifestyles through active breaks in administrative staff of the company Apuestas Ochoa SA in the city of Armenia. The aim of the project was to promote healthy habits and lifestyles in the administrative staff of a Betting Company named Ochoa S.A. through active pauses, carrying out activities such as breathing exercises, muscle stretching and playtime, among others, performed in a time span of 15 minutes Identifying unhealthy habits for intervention, and thus, putting into practice and implementing the active break schedule to promote healthy lifestyles and habits, and finally reflect on the intervention process using a questionnaire. The methodology of a research project was implemented in three main periods meant for the development of the work plan; among them is the diagnosis, the construction of the work plan based on the data obtained and the intervention established in the administrative headquarters of the company. As a result there was a high degree of satisfaction in participation, both in the contribution of active breaks in work performance and the acquisition of healthy habits in lifestyles. It’s main objective was met, the activities contributed to the acquisition of more healthy lifestyles. It also evidenced the importance of the participation of the physical educator within public or private companies as well as the need and continuity of these types of interventions.